The Fiscal Management of Natural Resource Revenues in a Developing Country Setting (or How to Design a Fiscal Rule If You Are Not Norway) - Eckardt, Sebastian (World Bank, Washington, DC, 2013)
The exhaustibility and volatility of natural resource revenues pose well-known economic challenges, of which those facing oil producers are the most prominent. If oil revenues represent an important share of export earnings and of government revenues, then they can be part of overheating during booms and costly adjustments during downturns, making fiscal policy exacerbate volatility. At the same time, considerations of intergenerational equity suggest that fiscal policy should also preserve part of current oil revenues for future generations. To address both of these challenges, resource-rich countries commonly establish commodity funds, into which part of their resource-linked revenues are deposited and invested in income-generating assets (usually offshore financial assets). A key question in designing such funds is what share of current revenues should be spent and what share saved. Based on recent advisory services offered to the Ministry of Economy and Trade in Kazakhstan, this note summarizes one possible approach, aiming to provide rule-based anchors for sustainable fiscal policy in an oil-producing country. This approach applies traditional permanent-income and debt sustainability frameworks, but adapts the resulting recommendations to the institutional context of the country. Rule-based fiscal frameworks offer strong benefits to countries that are generating significant government revenue from extractive industries. As commitment devices, these frameworks can reinforce fiscally responsible economic management, contain volatility, and preserve fiscal savings for future generations.